Optimisation of drying process parameters for bitter guard drying - Kusat, Anil; Sahoo, A K; Lokhande, Siddharth; Mote, Gurunath; Udachan, Iranna (Journal of Postharvest Technology, 2021)
Bitter gourd (Momordica Chrantia) fruits were analyzed for its proximate composition. The results showed that it is a good source of vitamin C and proteins. The optimization of dehydration process for bitter gourd was done. Blanching pre-treatment was optimized on the basis of sensory quality. Blanching in plain water and in 5% salt water for 1,3,5 minute was accomplished and the sensory quality of the blanched bitter gourd slices before and after drying were observed. Bitter gourd slices were dried in a cabinet tray dryer at temperatures 50 0C, 60 0C and 70 0C. Temperature for drying was optimized on the basis of parameters such as drying rate, drying time required, moisture in final product, yield of powder and sensory quality. Slices were then grinded to powder. The packaging and shelf life study of bitter gourd powder was carried out. From this research work it was found that the blanching of bitter gourd slices in plain water for 3 minute and drying at 60 °C resulted in the best quality product. The developed bitter guard powder was rich source of protein, vitamin C was safely stored at room temperature for three months.